Velocity extraction of nonlinear internal waves by reverberation detecting in shallow water waveguide - Gao, Bo; Li, Gongyun; Pang, Jie (Frontiers in Marine Science, 2024)
In the realm of shallow water acoustics, reverberation poses a critical challenge to active sonar systems, yet it also serves as a valuable conduit for environmental information. This study presents the findings from a 48-hour experimental investigation of reverberation and clutter in the northern Yellow China Sea, conducted in July 2014. Utilizing temperature and depth sensor arrays, we captured multiple instances of nonlinear internal waves (NIWs). Notably, the reverberation data collected by a vertical array of hydrophones revealed peculiar intensity fluctuations, which were exclusively detected by hydrophones located below the thermocline as NIWs traversed the measurement vessel. To elucidate this phenomenon, we introduce a novel coupled-mode reverberation–clutter theory. Through numerical computations, we determined both the coherent and incoherent components of the reverberation intensities, effectively accounting for the observed target-like intensity variations. The model developed herein was further employed to successfully estimate the velocity of NIWs. These anomalous reverberation characteristics could potentially pave the way for innovative methods of NIW parameter detection in shallow water environments.